Systematics of the Neotropical braconid wasps of the Pedinotus genus group (Doryctinae). (14th January 2016) - SAMACÁ‐SÁENZ, ERNESTO; BELOKOBYLSKIJ, SERGEY A.; QUICKE, DONALD L. J.; ZALDÍVAR‐RIVERÓN, ALEJANDRO
Abstract: The braconid subfamily Doryctinae (Hymenoptera) is a cosmopolitan, species‐rich group of parasitoid wasps whose known species richness and morphological diversity is mainly concentrated in the Neotropical region. Among the doryctine taxa that are endemic to this region, there is a group of six genera (the Pedinotus genus group) that are mainly characterized by having lateral, posteriorly converging or subparallel grooves on the second metasomal tergite (including Gymnobracon Szépligeti, Hybodoryctes Szépligeti, Lamquetia Braet et van Achterberg, Osmophila Szépligeti, Pedinotus Szépligeti and Trigonophasmus Enderlein). Most of these genera were described more than a century ago, and thus their limits and diagnostic morphological features are not well defined. We present an analysis of the phylogenetic relationships among various representative species of five of the six genera belonging to the Pedinotus genus group based on one mitochondrial (cytochrome oxidase I) and two nuclear (28S, Wingless ) gene markers. We also estimated the timing of origin and diversification within the group and investigated the external morphology of the genera involved in order to determine reliable identification characters. The group as a whole, whilst being recovered as monophyletic with the inclusion of Acanthorhogas Szépligeti, was not statistically supported. However, the respective monophyly of all of the morphologically supported genera are confirmed, as are the intergeneric relationships ( Gymnobracon, Trigonophasmus ) (( Acanthorhogas, Osmophila ) ( Lamquetia, Pedinotus )). We propose that the pattern of sublateral grooves or depressions appears to be a useful systematic character for recognition of an endemic Neotropical radiation that could have originated c. 41–27 Ma. We redescribe six of the seven genera that we recognize for the Pedinotus genus group and provide a key to enable their identification.